Measurement of transformational leadership in South Africa: Assessed from an etic perspective - Sonja Grobler; Anton Grobler (SA Journal of Industrial Psychology, 2023)
Orientation: It is scientifically questionable whether a predominantly Western construct and instrument could be used in the culturally diverse South African context. The sound measurement of transformational leadership in a multicultural context with the Transformational Leadership Questionnaire (TLQ), developed by Podsakoff et al. (1990), is studied from an etic perspective.